Growth of Tourism in India - Contributions by Domestic Travelers - Nair, Radhika Bhakthavalsalan (2015)
In this study we intend to identify the factors affecting domestic tourism in India. Past studies had provided variables such as climatic conditions, price, and destination management as affecting choice of tourism destination. The sample was broadly from south India and the findings revealed that climate and destination management inclusive of destination marketing and image had a higher influence on choice of consumers. For the middle class population, it was noted that price and destination management was more significant than the climate variable. These findings have significant policy implications such that promoting or advertising tourism in India should be done in an effective and efficient way as the destination marketing and image plays a crucial role. For the middle class population, in particular, the Ministry of tourism must ensure that the price is affordable by providing discounts and promotional offers. This study thus could be a benchmark for tourism policy makers and destination managers in India.